Photoelectric conversion element
By adopting a multi-layer structure in the second electrode of the perovskite-type photoelectric conversion element, using the laminated structure of different metals and their oxides and oxygen concentration control, the perovskite-type photoelectric conversion element is easily corroded in the external environment and The problem of insufficient electronic efficiency achieves higher electronic efficiency and conductivity and stronger barrier capabilities.
Patent Information
- Application Number
- CN202410270748.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-05
- Filing Date
- 2024-03-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing perovskite-type photoelectric conversion elements are prone to corrosion in the external environment, resulting in deterioration of characteristics and insufficient electronic efficiency and conductivity.
The second electrode adopts a multi-layer structure, including at least one first metal and oxide selected from the group consisting of titanium, tin, zinc, cerium, indium and niobium, and the second metal and oxide above thereof. The substance layer is controlled by controlling the oxygen concentration in different regions to improve barrier capacity and electrical conductivity.
The electronic efficiency and conductivity of the photoelectric conversion element are effectively improved, while the barrier ability to the external environment is enhanced, and the characteristics are suppressed.
Smart Images

Figure CN119451373A_ABST
Abstract
Description
[0001] This application is based on Japanese Patent Application No. 2023-125470 (filing date: 8 / 1 / 2023) and Japanese Patent Application No. 2024-032815 (filing date: 5 / 3 / 2024), and enjoys priority from the above applications. This application incorporates all the contents of the above applications by reference. Technical Field
[0002] An embodiment of the present invention relates to a photoelectric conversion element. Background Art
[0003] Photoelectric conversion elements such as solar cells, optical sensors, light-emitting elements, photodiodes, and optical memories using perovskite materials as photoelectric conversion materials can be used in layers to form inexpensive coating methods, so they can be expected to be low-cost photoelectric conversion elements. Among the perovskite materials used as photoelectric conversion materials, perovskite crystals having a composition represented by ABX3 and a three-dimensional crystal structure have excellent photoelectric conversion efficiency, so solar cells that use them to improve conversion efficiency have been reported. As one of the topics of such solar cells, the corrosion resistance and conductivity of the electrode (cathode) formed on the photoelectric conversion layer can be listed.
[0004] The photoelectric conversion element using perovskite materials, for example, has a structure in which an anode, a photoelectric conversion layer, an electron transport layer and a cathode are stacked on a transparent substrate. In such a photoelectric conversion element, for the cathode, a layer comprising chromium (Cr) and Cr oxide and a layer stacked structure of gold (Au), copper (Cu), aluminum (Al), etc. formed thereon are proposed. However, since Cr oxide is a p-type semiconductor, it will become a barrier to electron transport when it is configured on the electron transport layer side, thereby causing a decrease in efficiency. Furthermore, since only one layer comprising an oxide is configured in the cathode, it is impossible to fully improve the blocking ability from the external environment. Therefore, the Au layer on the upper side is prone to degradation due to corrosion from the external environment. Summary of the invention
[0005] The problem to be solved by the present invention is to provide a photoelectric conversion element having improved electron efficiency and conductivity while sufficiently improving the shielding capability from the external environment and suppressing the degradation of characteristics.
[0006] The photoelectric conversion element of the embodiment comprises: a substrate; a first electrode arranged on the above-mentioned substrate; a photoelectric conversion film, which is arranged on the above-mentioned first electrode and contains perovskite crystals having a composition represented by the following composition formula; an electron transport layer arranged on the above-mentioned photoelectric conversion film; and a second electrode arranged on the above-mentioned electron transport layer.
[0007] Composition formula: ABX3
[0008] (In the formula, A is a monovalent cation of an amine compound, B is a divalent cation of a metal element, and X is a monovalent anion of a halogen element.)
[0009] In the photoelectric conversion element of the embodiment, the second electrode comprises: a first layer, which is arranged on the electron transport layer and includes at least one first metal selected from the group consisting of titanium, tin, zinc, cerium, indium and niobium and an oxide of the first metal; and a second layer, which is arranged on the first layer and includes a second metal and an oxide of the second metal, and the second layer comprises: a first region existing on the first layer side; a second region existing on the first region and having an oxygen concentration lower than that of the first region; and a third region existing on the second region and having an oxygen concentration higher than that of the second region. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a cross-sectional view showing a first example of the photoelectric conversion element according to the embodiment.
[0011] Figure 2 It is a cross-sectional view showing a second example of the photoelectric conversion element according to the embodiment.
[0012] Figure 3 This is an IV curve diagram of the photoelectric conversion element of Example 1.
[0013] Figure 4 This is an IV curve graph of the photoelectric conversion element of Comparative Example 1.
[0014] Figure 5 This is an enlarged photograph showing the state of the Al electrode of the photoelectric conversion element of Example 1 100 hours after preparation.
[0015] Figure 6 This is an enlarged photograph showing the state of the Al electrode of the photoelectric conversion element of Comparative Example 1 100 hours after the preparation.
[0016] Figure 7 This is a diagram showing the results of XPS analysis of the Al components in the portions corresponding to the third region, the second region, and the first region in the Al electrode of the photoelectric conversion element of Example 1.
[0017] Figure 8 This is a diagram showing the XPS analysis results of the Ti component near the first region of the photoelectric conversion element of Example 1.
[0018] Fig. 9 This is a graph showing the abundance ratio of elements in the Al electrode and the Ti electrode in the photoelectric conversion element of Example 1.
[0019] Fig.10This is a diagram showing the results of XPS analysis of the Al components in the portions corresponding to the third region, the second region, and the first region in the Al electrode of the photoelectric conversion element of Comparative Example 1.
[0020] Fig.11 This is a graph showing the element abundance ratio of the Al electrode and the Ti electrode in the photoelectric conversion element of Comparative Example 1.
[0021] (Explanation of Symbols)
[0022] 100 ...photoelectric conversion element, 110 ...substrate, 120 ...first electrode, 130 ...photoelectric conversion film, 140 ...electron transport layer, 150 ...second electrode, 160 ...first layer, 170 ...second layer, 171 ...first region, 172 ...second region, 173 ...third region, 180 ...third layer. DETAILED DESCRIPTION
[0023] Hereinafter, the photoelectric conversion element and the manufacturing method thereof of the embodiment will be described with reference to the accompanying drawings. It should be noted that in each embodiment, the same symbol is sometimes marked for substantially the same component, and a part of the description is omitted. The accompanying drawings are schematic diagrams, and the relationship between the thickness and the plane size, the ratio of the thickness of each part, etc. are sometimes different from the actual situation. The terms indicating the direction such as up and down in the description indicate the relative direction of the case where the formation surface of each layer of the substrate described later is taken as the upper side, unless otherwise specified, which is sometimes different from the actual direction based on the direction of gravitational acceleration.
[0024] Figure 1 It is a cross-sectional view showing a first example of the photoelectric conversion element according to the embodiment. Figure 1 The photoelectric conversion element 100 shown in FIG. 1 includes a transparent substrate 110 as a supporting substrate, a first electrode 120 disposed on the transparent substrate 110, a photoelectric conversion film 130 disposed on the first electrode 120, an electron transport layer 140 disposed on the photoelectric conversion film 130, and a second electrode 150 disposed in the electron transport layer 140. Each constituent layer will be described in detail below.
[0025] Here, since the photoelectric conversion element 100 is assumed to be the second electrode 150 irradiated with light from the lower side in the drawing, a transparent substrate 110 is used as the supporting substrate. For the transparent substrate 110, a material having light transmittance and insulation is used. For the constituent material of the transparent substrate 110, inorganic materials such as alkali-free glass, quartz glass, and sapphire, and organic materials such as polyethylene (PE), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide, polyamide, polyamide-imide, and liquid crystal polymer are used. The transparent substrate 110 can be a rigid substrate formed of an inorganic material or an organic material, or a flexible substrate formed of an organic material or an extremely thin inorganic material.
[0026] The first electrode 120 disposed on the transparent substrate 110 is a transparent electrode as an anode, and is composed of a material having light transmittance and conductivity. As a constituent material of the first electrode 120, conductive metal oxides such as indium oxide, zinc oxide, tin oxide, indium tin oxide (ITO), fluorine-doped tin oxide (FTO), indium-zinc oxide (IZO), indium-gallium-zinc oxide (IGZO), conductive two-dimensional layered compounds such as titanium carbide or titanium aluminum carbide, thin films of metals such as gold, platinum, silver, copper, titanium, zirconium, cobalt, nickel, indium, aluminum, or alloys containing these metals, conductive polymer materials such as poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonic acid) (PEDOT / PSS), carbon compounds such as graphene or carbon nanotubes, etc. can be listed. The first electrode 120 is formed, for example, by vacuum evaporation, sputtering, ion plating, plating, coating, etc.
[0027] The photoelectric conversion film 130 is a perovskite crystal layer. The perovskite crystal has a composition represented by the following formula (1) and has a three-dimensional crystal structure.
[0028] Composition formula: ABX3…(1)
[0029] In the formula (1), A is a monovalent cation of an amine compound, B is a divalent cation of a metal element, and X is a monovalent anion of a halogen element.
[0030] Perovskite crystal structures are divided into four types from zero-dimensional structures to three-dimensional structures. A two-dimensional structure having a composition represented by A2BX4 and a three-dimensional structure having a composition represented by ABX3 are advantageous in obtaining a highly efficient photoelectric conversion material and a photoelectric conversion element using the same. Among these, it is known that the binding energy of the excitons of the three-dimensional structure is low, and it is more preferred in obtaining a highly efficient photoelectric conversion material and a photoelectric conversion element. It is known that a two-dimensional structure is used when the ion radius of the A site is large, and a three-dimensional structure is used when it is small.
[0031] It is known from experience that when the A-site ion has an ionic radius with a tolerance factor t between 0.75 and 1.1, a three-dimensional perovskite crystal is formed. The tolerance factor t is a value represented by the following formula (2). There are several types of ionic radius, but the Shannon ionic radius is used.
[0032] t = (A site ionic radius + X site ionic radius) / {2 1 / 2 ×(B site ionic radius + X site ionic radius)}…(2)
[0033] In order to satisfy the above-mentioned conditions of the A site ion, the A site is composed of a monovalent cation of an amine compound. The amine compound constituting the A site is preferably at least one selected from methylammonium (CH3NH2) and formamidinium (NH2CHNH). The B site is composed of a divalent cation of a metal element, and the X site is composed of a monovalent anion of a halogen element. The metal element constituting the B site is preferably at least one selected from lead (Pb) and tin (Sn). The halogen element constituting the X site is preferably at least one selected from iodine (I), bromine (Br) and chlorine (Cl). Through them, a high photoelectric conversion efficiency can be obtained.
[0034] The thickness of the photoelectric conversion film 130 is preferably in the range of 10 to 1000 nm. The photoelectric conversion film 130 may be applied, for example, by the following method of applying a photoelectric conversion material dispersion: a dispersion of a coating liquid (perovskite crystal) obtained by dispersing a photoelectric conversion material such as a perovskite crystal in a dispersion is applied to the transparent substrate 110, and the dispersion is scattered and dried to form a perovskite crystal layer. As a coating mechanism for the photoelectric conversion material dispersion, any method (and mechanism) can be used as long as it can supply the photoelectric conversion material dispersion to the film-forming object with a uniform film thickness. For example, liquid coating methods such as spin coating, slit coating, screen printing, spraying, and meniscus coating can be applied.
[0035] The photoelectric conversion film 130 is irradiated with light such as sunlight or illumination light from the transparent substrate 110 side. When the photoelectric conversion film 130 formed of the perovskite crystal layer absorbs the light irradiated to the photoelectric conversion element 100, electrons and holes paired therewith are generated. Among the electrons and holes generated in the photoelectric conversion film 130, for example, electrons are captured by the second electrode (cathode) 150 via the electron transport layer 140, and holes are captured by the first electrode (anode) 120. A hole transport layer may also be configured between the first electrode 120 and the photoelectric conversion film 130.
[0036] The electron transport layer 140 has the function of blocking holes generated in the photoelectric conversion film 130 and selectively and efficiently transporting electrons to the second electrode 150. For the electron transport layer 140, metal oxides such as zinc oxide, titanium oxide, and gallium oxide, fullerene C 60 , C 70 、Fullerene metal complex、[6,6]phenyl C 61 Methyl butyrate (PC60BM), [6,6]phenyl C 71 Methyl butyrate (PC70BM), biindene C 60(60ICBA) and other fullerene derivatives, polyethyleneimine, perylene diimide derivatives, naphthalene diimide derivatives and other organic materials. In the case of a hole transport layer, the hole transport layer has the function of blocking the electrons generated in the photoelectric conversion film 130 and selectively and efficiently transporting the holes to the first electrode 120. For the hole transport layer, organic conductive polymers such as PEDOT / PSS, polythiophene, polytoluidine, polypyrrole, triphenylene diamine polypyrrole, polyaniline, nickel oxide, copper oxide, tungsten oxide, molybdenum oxide, vanadium oxide and other metal oxides, carbazole compounds or polycyclic aromatic compounds having a phosphoric acid part or a carboxylic acid, a silyl ester part that can form a chemical bond with the first electrode 120 are used. The electron transport layer is formed by a vacuum film forming method such as a vacuum evaporation method or a sputtering method, a sol-gel method, a coating method, etc. The same is true for the hole transport layer.
[0037] The second electrode 150 is made of a material having electrical conductivity and, if necessary, light transmittance. The second electrode 150 includes: a first layer 160, which is disposed on the electron transport layer 140 and includes at least one first metal selected from the group consisting of titanium (Ti), tin (Sn), zinc (Zn), cerium (Ce), indium (In), and niobium (Nb), and an oxide of the first metal; and a second layer 170, which is disposed on the first layer 160 and includes a second metal and an oxide of the second metal. As the second metal, it is preferably a metal having a higher electrical conductivity than the first metal, for example, at least one selected from the group consisting of aluminum (Al), molybdenum (Mo), nickel (Ni), copper (Cu), and silver (Ag). Each layer of the second electrode 150 is formed by a vacuum film forming method such as a vacuum evaporation method or a sputtering method.
[0038] The second layer 170 in the second electrode 150 includes a first region 171 existing on the first layer 160 side, a second region 172 existing on the first region 171, and a third region 173 existing on the second region 172. The first region 171 has a higher oxygen concentration than the second region 172. In other words, the second region 172 has a lower oxygen concentration than the first region 171. Furthermore, the third region 173 has a higher oxygen concentration than the second region 172. The first region 171 and the third region 173 are preferably not in a state where oxygen is simply contained or in a state where oxygen is simply adsorbed on the surface, but in a state where the second metal is bonded to oxygen. The first region 171 and the third region 173 having such a state are excellent in corrosion resistance.
[0039] In the first layer 160 of the second electrode 150, at least one first metal selected from the group consisting of Ti, Sn, Zn, Ce, In, and Nb, which constitutes the first layer 160, exhibits properties as an n-type semiconductor in the form of an oxide, and therefore does not prevent the electrons generated in the photoelectric conversion film 130 from being captured by the second electrode (cathode) 150 via the electron transport layer 140, but promotes the movement of the electrons. Therefore, the efficiency of the photoelectric conversion element 100 is improved. Furthermore, the oxide of the first metal is excellent in corrosion resistance, and therefore contributes to the improvement of the corrosion resistance of the second electrode 150.
[0040] By forming the second layer 170 including, for example, a second metal having higher conductivity than the first metal and an oxide of the second metal on the first layer 160 including the first metal and an oxide of the first metal, the second electrode 150 is made into a stacked electrode of the first layer 160 including the oxide of the first metal and the second layer 170 including the oxide of the second metal, so that the ability to block the external environment can be improved. Therefore, it is possible to improve the electron efficiency of the photoelectric conversion element 100, and to sufficiently improve the ability to block the external environment of the second electrode 150, thereby suppressing the degradation of the characteristics of the second electrode 150 caused by contamination of the second electrode 150 from the external environment.
[0041] Furthermore, the second layer 170 in the second electrode 150 includes a first region 171 existing on the first layer 160 side, a third region 173 existing on the outermost layer side, and a second region 172 existing between them, and the first region 171 and the third region 173 each have a higher oxygen concentration than the second region 172. By using such a first region 171 and a third region 173, the barrier capability of the second layer 170 to the external environment can be improved. Furthermore, since the oxygen concentration of the second region 172 existing between them is lowered than that of the first region 171 and the third region 173, the conductivity of the second layer 170 brought about by the second region 172 can be improved. That is, the photoelectric conversion element 100 including the second electrode 150 having improved corrosion resistance by improving the conductivity originally required for the electrode and the barrier capability to the external environment can be provided.
[0042] In the second electrode 150, the first layer 160 preferably has a thickness of 1 nm to 50 nm, and the second layer 170 preferably has a thickness of 20 nm to 400 nm. In addition, in the second layer 170, the first region 171 preferably has a thickness of 1 nm to 30 nm, the second region 172 preferably has a thickness of 10 nm to 398 nm, and the third region 173 preferably has a thickness of 1 nm to 30 nm. The thicknesses of the first region 171, the second region 172, and the third region 173 in the second layer 170 can be determined by energy dispersive X-ray spectroscopy (TEM-EDX) in the cross-sectional direction using a transmission electron microscope, or X-ray photoelectron spectroscopy (XPS) in the depth direction combined with ion sputtering.
[0043] The first layer 160 and the second layer 170 in the second electrode 150 can be formed by a vacuum film forming method such as a vacuum evaporation method or a sputtering method. For example, when the vacuum evaporation method is applied to form the second electrode 150, the oxygen concentrations of the first region 171, the second region 172, and the third region 173 can be controlled by changing the pressure or oxygen concentration in the film forming chamber.
[0044] The second electrode 150 may further include Figure 2 As shown in , it has a third layer 180 arranged on the second layer 170 and containing a third metal. As the third metal constituting the third layer 180, for example, a metal that is difficult to oxidize than the second metal can be used. As such a metal, at least one selected from the group consisting of copper (Cu), silver (Ag) and gold (Au) can be listed. By applying the third layer 180 containing such a third metal, the conductivity of the second electrode 15 can be further improved. Alternatively, for the third metal, a metal that is easier to form a passivation than the second metal can also be applied. As such a metal, at least one selected from the group consisting of titanium (Ti), aluminum (Al) and molybdenum (Mo) can be listed. By applying the third layer 180 containing such a third metal, the corrosion resistance of the second electrode 15 can be further improved by using the passivated third layer 180.
[0045] The photoelectric conversion element 100 of the embodiment has a second electrode 150 that has improved corrosion resistance by improving the ability to block the external environment, and has improved electron efficiency and conductivity. Therefore, the photoelectric conversion element 100 with improved conductivity, electron efficiency and corrosion resistance can be provided. The photoelectric conversion element 100 of the embodiment can be applied to solar cells, optical sensors, light-emitting elements, photodiodes, optical memories, and the like.
[0046] Example 1
[0047] Next, examples and their evaluation results are described.
[0048] (Example 1)
[0049] [Fabrication of Photoelectric Conversion Element]
[0050] After forming an ITO film as the first electrode on a PET substrate, ultrasonic cleaning and UV cleaning in isopropyl alcohol and acetone were performed. On the PET substrate having an ITO film, a hole transport layer containing PEDOT:PSS with a thickness of about 50 nm was formed. PEDOT:PSS (AI4083 (trade name) manufactured by Heraeus Corporation) was used as the solution for the hole transport layer. A meniscus coating device with a cylindrical applicator was used for film formation. The applicator was configured so that the gap distance with the PET substrate became 0.2 mm, and 7.5 μL of the hole transport layer solution was supplied to each coating area of the applicator to form a meniscus column. The coating liquid was applied to the PET substrate while controlling the angle and gap distance of the PET substrate. The moving speed of the PET substrate was set to be constant at 8.0 mm / s. The hole transport layer solution was applied to the PET substrate having an ITO film, and then heated at 140°C in the atmosphere for 10 minutes to remove excess solvent and form a hole transport layer. The film thickness of the hole transport layer was about 50 nm.
[0051] Next, as a photoelectric conversion layer, a perovskite layer is formed as follows. First, methylammonium iodide (CH3NH3I) and lead iodide (PbI2) are dissolved in N,N-dimethylformamide (DMF) to prepare a perovskite material solution (coating solution). The coating solution sets the molar ratio of methylammonium iodide to lead iodide to 1:1, and adjusts the concentration in the solution to 45% by mass. For film formation, a curved liquid surface coating device with a cylindrical applicator is used. The applicator is configured so that the gap distance with the PET substrate becomes 0.2 mm, and 7.5 μL of the perovskite material solution is supplied to each coating area of the applicator to form a curved liquid surface column. The coating liquid is applied to the PET substrate while controlling the angle and gap distance of the PET substrate. The moving speed of the PET substrate was set to be constant at 100 mm / s. While coating, nitrogen gas at a wind speed of 6.0 m / s was blown onto the coating film by an air knife to dry the coating film. After that, the coating film was heated at 120°C for 10 minutes to remove excess solvent and grow crystals to form a photoelectric conversion layer of a perovskite crystal compound. The film thickness of the photoelectric conversion layer was about 500 nm.
[0052] Next, 1 mL of monochlorobenzene was added to 20 mg of 60PCBM to prepare a solution for the electron transport layer. The coating head was configured so that the gap distance with the photoelectric conversion layer on the PET substrate was 0.5 mm. 40.0 μL of the electron transport layer solution was supplied to each coating area of the coating head to form a curved liquid surface column. The coating liquid was applied to the PET substrate while controlling the angle and gap distance of the PET substrate. The moving speed of the PET substrate was set to be constant at 8.0 mm / s. After applying the solution of the electron transport layer on the ITO substrate, it was heated at 100°C in the atmosphere for 10 minutes to remove excess solvent and form an electron transport layer. The film thickness of the electron transport layer is about 50 nm.
[0053] Next, P2 scribing was performed by mechanical scribing. A cutter with a rectangular tip and a width of 80 μm was used as a scribing tool. The scribing tool was contact-pushed by a suspension mechanism using a spring, and P2 mechanical scribing was performed by scanning in parallel with the length direction of the ITO film, and the three layers of the electron transport layer, the perovskite layer, and the hole transport layer were removed to expose the ITO film.
[0054] Next, the second electrode (counter electrode) was formed. The vacuum degree was set to 1×10 -3 Pa, Ti was vacuum-deposited. The thickness of the Ti layer was 10 nm. Then, Al was vacuum-deposited at the same vacuum degree to form a film. The thickness of the Al layer was about 100 nm.
[0055] (Comparative Example 1)
[0056] A photoelectric conversion element was produced in the same manner as in Example 1, except that Ti was not formed in the film formation of the second electrode (counter electrode) of Example 1, but Al was formed in a 100 nm film by vacuum deposition.
[0057] [Evaluation of Initial Conversion Efficiency of Photoelectric Conversion Element and Evaluation after 100 Hours]
[0058] The IV characteristics of the photoelectric conversion elements of Example 1 and Comparative Example 1 were measured. The IV characteristics were measured using a solar simulator at 100 mW / cm 2 The measurement was carried out based on the radiation intensity of 1.5G and the reference spectrum of air mass (AM) 1.5G. The measurement was carried out on the initial conversion efficiency of the element just after production and the conversion efficiency 100 hours after production. The measurement results are shown in Figure 3 , Figure 4 And Table 1. Figure 3 is the IV curve of Example 1, Figure 4 It is an IV curve of Comparative Example 1, the dotted line represents the initial conversion efficiency immediately after the element is produced, and the solid line represents the conversion efficiency after 100 hours.
[0059] Table 1
[0060]
[0061] [Observation of the Counter Electrode of the Photoelectric Conversion Element]
[0062] The above-mentioned photoelectric conversion element was observed using an optical microscope. The second electrode (counter electrode) was observed 100 hours after production at an observation magnification of 10 times, and an enlarged photograph was taken. The results are shown in Figure 5 , Figure 6 And Table 2. Figure 5 The Al electrode of Example 1 is shown 100 hours after being produced. Figure 6 The state of the Al electrode of Comparative Example 1 after 100 hours of preparation is shown.
[0063] Table 2
[0064]
[0065] [XPS measurement of perovskite compound layer]
[0066] XPS analysis of the above-mentioned photoelectric conversion element was performed 100 hours after the production. Composition analysis in the depth direction was performed while scraping along the film thickness direction from the second electrode (counter electrode) side by sputtering. The analysis results are shown in Figure 7 to Figure 11 middle. Figure 7 The state of the Al component in the portions corresponding to the third region, the second region, and the first region of the photoelectric conversion element of Example 1 is shown. The signal around 76 eV corresponds to aluminum oxide, and the signal around 73 eV corresponds to metal aluminum. Figure 8 The Ti component near the first region is shown, and signals at around 455 eV and 461 eV correspond to metal titanium, and signals at 457 eV and 462 eV on the lower energy side correspond to titanium oxide. Fig. 9 It is a graph about the abundance ratio of elements when the horizontal axis is set to the depth direction. The upper part is a graph in which the abundance ratios of Al, Ti, and O are plotted on the vertical axis, and the lower part is a graph in which the ratio of O to Al is plotted. Fig.10 The signal indicating the state of the Al component in the portions corresponding to the third region, the second region, and the first region of the photoelectric conversion element of Comparative Example 1 is a signal corresponding to aluminum oxide at around 76 eV and to metal aluminum at around 73 eV. Fig.11 It is a graph about the abundance ratio of elements when the horizontal axis is set to the depth direction. The upper part is a graph in which the abundance ratios of Al and O are plotted on the vertical axis, and the lower part is a graph in which the ratio of O to Al is plotted.
[0067] As shown in Table 1, when the Ti electrode is stacked, the series resistance is low, the filling factor is high, and the short-circuit current density is improved, and the conversion efficiency is improved. It is believed that the formation of the high-resistance aluminum oxide film generated by the oxidation of the Al electrode is suppressed by forming the Ti electrode. After 100 hours of production, in the absence of the Ti electrode, the series resistance becomes large and the efficiency is greatly reduced. The appearance of the electrode is as follows Figure 6 According to the results of XPS analysis, Fig. 9 and Fig.11 As shown in Table 1, the signal of aluminum oxide is observed in a state where the ratio of oxygen to aluminum in the depth direction is greater. It is known that a thick film of aluminum oxide is formed in the film thickness direction, the surface changes, and the resistance increases. On the other hand, in the case of a Ti electrode, no decrease in conversion efficiency is observed, as shown in Table 1. Figure 5 In that case, no change in the appearance of the electrode was observed.
[0068] According to the results of XPS analysis, Figure 7 and Fig. 9 As shown in , in the third region corresponding to the surface layer of the Al electrode, the ratio of oxygen is higher than that of aluminum, and aluminum oxide is observed. In the second region inside, the ratio of aluminum is higher than that of oxygen. In the first region in contact with the Ti electrode, the ratio of oxygen is higher than that of aluminum, and a signal of aluminum oxide is observed. Fig. 9 It was found that the Ti electrode is a mixed layer of metal titanium and titanium oxide. Due to the above facts, the presence of titanium oxide having n-type semiconductor characteristics improves rectification, increases parallel resistance, and increases the filling factor, thereby increasing conversion efficiency. In addition, the durability is improved by the aluminum oxide in the first region and the titanium oxide in the Ti electrode, and the conductivity is maintained because the proportion of aluminum in the second region is high.
[0069] (Example 2)
[0070] In the film formation of the second electrode (counter electrode) of Example 1, Ti was vacuum-deposited to a film thickness of 10 nm, Al was vacuum-deposited to a film thickness of 100 nm, and Ag was vacuum-deposited to a film thickness of 10 nm. A photoelectric conversion element was produced in the same manner as in Example 1. It was confirmed that such a photoelectric conversion element also had good characteristics as in Example 1.
[0071] (Example 3)
[0072] In the film formation of the second electrode (counter electrode) of Example 1, Ti was vacuum-deposited to a film thickness of 10 nm, Al was vacuum-deposited to a film thickness of 100 nm, and then Ti was vacuum-deposited to a film thickness of 10 nm. A photoelectric conversion element was produced in the same manner as in Example 1, except that it was formed by vacuum-evaporating Ti to a film thickness of 10 nm. It was confirmed that such a photoelectric conversion element also had good characteristics as in Example 1.
[0073] It should be noted that several embodiments of the present invention have been described, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the subject matter of the invention. These embodiments and their variations are included in the scope and subject matter of the invention, and are also included in the invention described in the claims and their equivalents.
Claims
1. A photoelectric conversion element, comprising: a substrate; a first electrode disposed on the substrate; A photoelectric conversion film, which is disposed on the first electrode and includes a perovskite crystal having a composition represented by the following composition formula; an electron transport layer disposed on the photoelectric conversion film; and a second electrode disposed on the electron transport layer, Composition formula: ABX3 In the formula, A is a monovalent cation of an amine compound, B is a divalent cation of a metal element, and X is a monovalent anion of a halogen element. The second electrode comprises: a first layer, which is arranged on the electron transport layer and includes at least one first metal selected from the group consisting of titanium, tin, zinc, cerium, indium and niobium, and an oxide of the first metal; and a second layer, which is arranged on the first layer and includes a second metal and an oxide of the second metal. The second layer includes a first region present on the first layer side, a second region present on the first region and having a lower oxygen concentration than the first region, and a third region present on the second region and having a higher oxygen concentration than the second region.
2. The photoelectric conversion element according to claim 1, wherein The second metal has higher conductivity than the first metal.
3. The photoelectric conversion element according to claim 2, wherein The second metal is at least one selected from the group consisting of aluminum, molybdenum, nickel, copper, and silver.
4. The photoelectric conversion element according to any one of claims 1 to 3, wherein The first region and the third region have a bond between the second metal and oxygen.
5. The photoelectric conversion element according to any one of claims 1 to 4, wherein The second electrode further includes a third layer disposed on the second layer and containing a third metal.
6. The photoelectric conversion element according to claim 5, wherein The third metal includes a metal that is less easily oxidized than the second metal.
7. The photoelectric conversion element according to claim 6, wherein The third metal is at least one selected from the group consisting of copper, silver, and gold.
8. The photoelectric conversion element according to claim 5, wherein The third metal includes a metal that is more likely to be in a passive state than the second metal.
9. The photoelectric conversion element according to claim 8, wherein The third metal is at least one selected from the group consisting of titanium, aluminum, and molybdenum.
Citation Information
Patent Citations
Actuator for aerosol and aerosol product
JP2023125470A
Compositions and method for detecting human parvovirus nucleic acid and for detecting hepatitis a virus nucleic acids in singleplex or multiplex assays
JP2024032815A